Building world class universities in Yemen: exploring Yemeni higher education expert’s perceptions and thoughts - Al-haimi, Basheer; Daing Mohd Nasir, Ibrahim; Ab Hamid, Mohd Rashid (Blue Eyes Intelligence Engineering & Sciences Publication, 2019)
World Class Universities (WCU) have substantially grown in popularity over the past couple of decades. These entities have incentivized the use of research as a tool for economic growth, as the emphasis on education and research development has led the governments to include them as key aspects for their national economic strategies. However, in a country like Yemen, there is a gap in research and development when it comes to the enhancement of the education system and university academia. Thus, this paper aims to investigate the requirements, initiatives and suitable strategic approaches that are required in order to create WCUs in Yemen. This is done by collecting and assessing the perceptions of Yemeni higher education experts. In order to achieve this goal, a qualitative method has been utilized for the research methodology, with the data being collected using deep interview systems. The selected population for the interview are five experts in the relevant field. The results of the study indicate that there are several requirements, initiatives and strategic approaches that can be executed in order for a WCU to be created in Yemen. Consequently, the expectation is for the findings of this research to provide a basis and bedrock for further initiative and proposals that can be used to guide policy makers in Yemen on developing the higher education institutes to a level which can compete with other countries around the world.